Comparative Study of Lean Six Sigma Practices for Sustainability: A Blueprint for Post Covid-19 Pandemic - Akanmu, Muslim Diekola; Othman, Othman; Yousaf, Mohammed Fathi (UUM Press, 2022)
The global crisis caused by Covid-19 and its impact on the healthcare system has been far-reaching and challenging in virtually all countries. Lean six sigma in Malaysia has never improvised an account for this case of the uncommon event as it only focuses on daily operations and productions that are in stability and in alignment with the demand to capacity in an effective way. This study, therefore, attempts to compare and contrast the previous researches on lean practices, six sigma, industrial evolution, and healthcare sustainability to investigate where the paucity of literature lies and to deploy new strategies for the post-pandemic. Currently, the healthcare industry is motivated to update its conventional delivery systems to smart sophisticated systems due to the growing challenges within the services organization. The study found that integrating industrial revolution 4.0 technologies into the services optimizes sustainable healthcare management. As providing affordable, reliable, and safe healthcare while improving efficient performance remains challenging in the healthcare industry, this study posits that a hybrid of industrial revolution technologies, lean practices, and six sigma are enhancers of social, economic, and environmental sustainability. The study also reveals the significant contributions of operations and services management practices and how the strategic implementation of modern technologies and performance variation can improve sustainable performance in the healthcare sector.